ANALISIS CITRA JERUK SIAM DI KALANGAN KONSUMEN DI KOTA BATURAJA KABUPATEN OGAN KOMERING ULU (JASEP, 2017)
This study aimed to describe the image of Tangerine in the Baturaja City and analyze the relationship between image tangerine with factors that affect the image of tangerine in the Baturaja City. This research was conducted in the Baturaja City, Ogan Komering Ulu in January 2017. The method used in this study is a survey method whereas the sampling method used in this research is accidental sampling method (sampling based on accident). The results showed that the image of an orange Siamese Baturaja City, Ogan Komering Ulu classified in the category quite well, it is seen from the large number of consumers who give these answers during the interview at the study site and index the results of the percentage of 64.66% means that the consumer will answer tangerine classified image good enough is strong. the results of the analysis of the test spearman rank (????????) using SPSS (Statistical Package for Social Science) showed a significant relationship between image tangerine with factors that affect the image of tangerine in Baturaja City, Ogan Komering Ulu. significant relationships is the relationship between the price of the image (correlation coefficient ???????? = 0.895 which means the correlation is very strong), the relationship between the sense of the image (correlation coefficient ????????= 0.921 which means the correlation is very strong), and the relationship between the ease with imagery (correlation coefficient ????????= 0.921 which means the correlation is very strong), while the relationship between the benefits to the image and the image quality is not significant because it is the value of t > ????0,05 or reject ????1 and accept ????0 means there is no relationship between the benefits to the image and quality with the image.